Dialogue：Qiu Linchuan and Wang Weijia on health communication from the perspective of the Global South - Gao, Rong; XU, Jing (The Journal of Medicine, Humanity and Media, 2023)
What is the Global South? What is health? Adopting a southern perspective must be a non-mainstream in communication studies? Health communication must be a quantitative research with substantial fundin.？In the form of casual discussion, Professor Qiu Linchuan started from Ev Rogers, who is famous for his theory of innovation diffusion. On the basis of reviewing his academic track, he found that research on health communication in the global South in a broad sense, involving multiple topics such as entertainment, education, participatory development, communication, empowerment, South-South cooperation, Empire platform, economy and health in the global South is a collection of empirical and speculative research The interdisciplinary field that combines theory with practice is so colorful and its charm is enduring, but it also faces severe challenges and crises, and needs the intervention of academic and policy research. After this, Professor Qiu Linchuan and Professor Wang Weijia have a dialogue on health communication from the perspective of the global South